REGULATORY AND FUNCTIONAL FRONTIERS IN PRECISION ONCOLOGY - MURTHANNAGARI, VIVEK REDDY; MOORTHY, KARUNAKARAN; AHMED, SYED SUHAIB; MADAR, INAMUL HASAN (International Journal of Applied Pharmaceutics, 2026)
Precision oncology has come a long way, largely thanks to our growing understanding of the molecular changes that drive cancer. By identifying these alterations, researchers and clinicians can now tailor treatments more effectively, offering what’s often called the right drug for the right patient at the right dose and at the right time. This approach has opened new possibilities in how we classify diseases, design clinical trials and use biomarkers and health technology to guide decisions. Modern tools like next-generation sequencing (NGS), RNA analysis and immune profiling have made it possible to analyse tumours and even detect genetic material like cell-free DNA from blood samples. These technologies help identify specific mutations or markers that could influence treatment. However, while the potential is enormous, there are still some challenges. For example, interpreting large volumes of genetic data can be tricky and there’s always the risk of false positives or unexpected findings. Plus, whole-genome sequencing and transcriptome profiling can still be expensive and time-consuming. To keep pace, regulatory agencies like the FDA in the U. S. and the EMA in Europe have put frameworks in place to ensure that precision therapies are developed responsibly. The FDA, for instance, encourages simultaneous development of diagnostics and treatments. Meanwhile, the UK’s MHRA has launched initiatives like the Precision Medicine Catapult to speed up innovation and translation from lab to clinic. Looking ahead, scientists are exploring even more refined strategies, such as functional precision oncology. Instead of relying solely on genetic sequencing, this approach incorporates real-time data about how tumours behave and respond to drugs, offering a more dynamic and personalised way to choose the most effective treatment.